Implementation of social responsibility accounting in PT. Perkebunan Nusantara III (Persero) Medan - Irwani Amabel Odelia Aritonang; Amran Manurung; Magdalena Judika Siringoringo; Mangasa Sinurat; Toman Sony Tambunan (Jurnal Mantik, 2023)
The purpose of this study is to find out whether social responsibility has been carried out in accordance with the provisions of Law No. 40 of 2007, as well as to find out how the form of Corporate Social Responsibility (CSR) Reporting, as well as what are the obstacles in carrying out social responsibility. The type of data used in this study is primary data with data collection methods using qualitative analysis techniques, in the form of interviews, documentation, and literature studies. The results of data analysis and discussion show that the company has not been able to meet the maximum interval of 3% of the amount of CSR funds stipulated in Law No. 40 of 2007, as well as in the form of CSR reports carried out by the company, which include annual reports, management reports, and sustainability reports on social activities and the costs realized are more disclosed in management reports and sustainability reports (Sustainability Report). While in the annual report it is only recorded as an administrative expense. This is an obstacle where CSR is carried out by the company as a burden not as a profit for the company. So that the company has implemented the application of social responsibility accounting is not in accordance with the amount of CSR funds has not been in accordance with standardization